2010
DOI: 10.1002/humu.21225
|View full text |Cite
|
Sign up to set email alerts
|

MultipleLRRK2variants modulate risk of Parkinson disease: a Chinese multicenter study

Abstract: We and others found two polymorphic LRRK2 (leucine-rich repeat kinase 2) variants (rs34778348:G>A; p.G2385R and rs33949390:G>C; p.R1628P) associated with Parkinson disease (PD) among Chinese patients, but the common worldwide rs34637584:G>A; p.G2019S mutation, was absent. Focusing exclusively on Han Chinese, we first sequenced the coding regions in young onset and familial PD patients and identified 59 variants. We then examined these variants in 250 patients and 250 control subjects. Among the 17 polymorphic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(127 citation statements)
references
References 24 publications
(36 reference statements)
8
117
2
Order By: Relevance
“…The R1398H LRRK2 polymorphism is quite common (>5 %) in several populations and apparently plays a protective role against development of PD [102,[106][107][108][109]. The R1398 residue is located in the switch II motif of the ROC domain and could be important for the interaction with the γ-phosphate of GTP [87].…”
Section: Lrrk2 Polymorphisms That May Affect Protein Functionmentioning
confidence: 99%
“…The R1398H LRRK2 polymorphism is quite common (>5 %) in several populations and apparently plays a protective role against development of PD [102,[106][107][108][109]. The R1398 residue is located in the switch II motif of the ROC domain and could be important for the interaction with the γ-phosphate of GTP [87].…”
Section: Lrrk2 Polymorphisms That May Affect Protein Functionmentioning
confidence: 99%
“…Before Ross et al study, there have been 4 articles exploring the associations between A419V and PD, yet none of them showed the p-value < 0.05 (Di Fonzo et al, 2006;Jasinska-Myga et al, 2010;Nuytemans et al, 2009;Tan et al, 2010). The total number of Asian PD patients and controls in Ross et al study is large but when dividing the number into 3 different countries, it is much smaller: Taiwan, 369 PD patients; South Korea, 830 PD patients; Japan, 177 PD patients.…”
Section: Discussionmentioning
confidence: 82%
“…However, a lot of replications showed controversial results (Di Fonzo et al, 2006;Gopalai et al, 2013;Li et al, 2012;Tan et al, 2010;Wu et al, 2012;Wu-Chou et al, 2013). Herein, we conducted a case-control study to explore the potential associations between A419V and PD in Chinese population and conducted a meta-analysis centering on Asian population.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…16,17,[34][35][36][37][38][39] One of these studies included 26 patients with a familial history of PD, among which six patients were p.G2385R carriers. 40 A meta-analysis on the basis of these studies involving 2205 PD patients and 1817 controls demonstrated average carrier rates of 9.3% in PD and 4% in controls.…”
Section: Discussionmentioning
confidence: 99%